Contribuições da análise do comportamento à superação de desafios que se interpõem ao desenvolvimento do esporte educacional - Paiva, Rodrigo (2011)
The sport is one of the most important and complex international phenomenon of the last centuries. A nation´s success in sports altogether with its own political, ideological and financial system resulted in international manifestos for a reinterpretation of the sport. In this context, the so called dimensions of the sport gave rise to an understanding of ii asboth as income, education and leisure. The educational sport (ES) must be understood as the educational practice of the sports aiming a person´s whole development and the exercise of citizenship However, since the emergence of this concept there has been little progress in developing effective methodologies that insert the practice of the sport into a person´s universal rights.. The development of ES copes with several challenges ; however, it is the assumption of this research that numbers of contributions made to education by the Experimental Analysis of Behavior (EAB) may also contribute to overcoming these challenges and build methodological assumptions that guide the capacitation and action of teachers in the educational dimension of sport. The objectives of this study were: 1. To trace down the of the themes Sport Psychology (SP), and EAB - SE. To spot possible EAB´s contributions for the construction of pedagogical guidelines to serve as reference for institutions and professional acting in sport and education and who wish to work in the educational dimension of sport. To do so, 2.266 articles and abstracts published between 2000 and 2010 in journals of physical education, SP and EAB were analyzed. The results showed that less than 5% of the articles´content were related to the SP and less than 0.5%, to SP. No publication promoted discussions regarding EAB´s contributions to both ACS SE and SP. The book Technology of Teaching, by BF Skinner (1968/1972), served as a reference for methodologies leading to the application of the knowledge produced by EAB, in educational settings, to overcome the challenges that stand to development of SE. The constitution of what is intended to be called as Educational Sport Psychology based on the Experimental Analysis of Behavior is a story yet to be told